New Faiths, Old Fears: Muslims and Other Asian Immigrants in American Religious Life by Bruce B. Lawrence (New York: Columbia University Press, 2002. 197 pages.) (American Journal of Islam and Society, 2006)
Bruce Lawrence’s book, New Faiths, Old Fears: Muslims and Other AsianImmigrants in American Religious Life, seeks to remedy theoretical gaps bycorrecting the emphasis on East Asians within Asian-American studies andby describing Asian Americans in relation to other minorities and dominantAnglos within the prevailing ethno-racial system (p. xiv). As a religiousstudies scholar with “a lifelong engagement with Islam, and an exuberantattachment to South Asia” (p. 38), he discusses post-1965 immigration andunderscores its religious and cultural dimensions. The range of controversialtopics broached in this book promise to appeal to a broad readership.Topics covered include historical and politico-economic aspects of immigration, racial prejudice, cultural and religious fundamentalism, argumentsover multiculturalism, transnational identities, and media representations ofreligion. Consequently, New Faiths, Old Fears is highly significant forthose interested in religious studies, sociology, anthropology, history, andcultural studies – and especially for those interested in immigration andAsian Americans ...